74‐1: Application of Transfer Technology to Manufacturing of Transmissive OLED and Reflective LC Hybrid (TR‐Hybrid) Display. Issue 1 (May 2016) - Ohide, Takayuki; Yasumoto, Seiji; Nakada, Masataka; Adachi, Hiroki; Idojiri, Satoru; Okazaki, Kenichi; Hirakata, Yoshiharu; Bergquist, Johan; Yamazaki, Shunpei
Abstract : Our previously established transfer technology using an inorganic separation layer was applied to enable a novel through electrode structure including a conductive material exposed after separation. Using this structure, we succeeded in fabricating a transmissive OLED and reflective LC hybrid display.